Digital Marketing Strategy for Sustainable Ecotourism Development: A BCG Matrix Analysis to Support SDG 8 and SDG 11 - Anang Martoyo; Neneng Rachmalia Feta; Rika Astuti; Siti Nuryati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To identify the business position of Ciwaluh Ecotourism Village and formulate an appropriate digital tourism marketing strategy to support its development and competitiveness. Method: A case study approach was employed using digital marketing strategy analysis through the Boston Consulting Group (BCG) Matrix. The analysis assessed market growth rate and relative market share by comparing Ciwaluh Ecotourism Village with its competitors. Results: The BCG Matrix analysis revealed a market growth rate of 12.81% and a relative market share of 1.82, placing Ciwaluh Ecotourism Village in the “Star” quadrant. The findings indicate the need for business expansion, government support, infrastructure development, and the utilization of digital platforms to improve tourism information access and marketing effectiveness. Novelty: BCG Matrix as a strategic digital marketing framework to support sustainable ecotourism village development. By integrating market growth and competitive positioning with digital marketing strategies, the study provides a data-driven decision-making model that contributes to the achievement of SDG 8 (Decent Work and Economic Growth) and SDG 11 (Sustainable Cities and Communities) through sustainable tourism development and improved destination competitiveness.